Legal Paradigm Shifts In The Age Of Digital Transformation - Galang Taufani; I Putu Endra Wijaya Negara (Realism: Law Review, 2026)
Digital transformation has reshaped the foundations of law, not only technologically but also normatively and methodologically. Legal paradigms in the digital era must be examined through systematic interpretation, doctrinal reasoning, and normative critique. This study, based on normative legal research with a conceptual approach, utilizes legal materials from books and scholarly journals. Findings reveal three major challenges: first, a legal vacuum and regulatory lag, as technological innovation outpaces regulation, leaving many digital activities ungoverned. Second, a jurisdictional crisis arises because territorially bound national legal systems cannot effectively regulate global digital interactions. Third, regulatory fragmentation occurs due to overlapping digital regulations, creating legal uncertainty. Consequently, the effectiveness of law in the digital age is not measured by the number of regulations but by its adaptability, integrative capacity, and progressive interpretation in response to technological dynamics. Without such transformation, law risks irrelevance in governing digital society